How to Improve the Protection of Employees-Whistleblowers in Slovenia by Implementing the EU Whistleblower Protection Directive - Senčur Peček, Darja (Towards a Better Protection of Workplace Whistleblowers in the Visegrad Countries, France and Slovenia, 2021)
Workers and public employees reporting unlawful or harmful conduct in Slovenia are granted special protection only by specific acts, whereas they also enjoy general labour-law protection as employees. The paper addresses the state of their protection as provided by the applicable sectoral legislation relating to the prevention of corruption and to reporting of irregularities in banking and financial sectors, as well as by general labour legislation. Based on the analysis of the material and personal scope of the existing protection, the regulation of reporting channels, the possibility of public disclosure, the legally defined protective measures, and the institutional framework, the author adopts a position on the possibility to update this protection by proper implementation of the EU Directive 2019/1937.